Application of the Method of Pairwise Comparisons When Combining Economic Forecasts - A. A. Surkov (Учёт. Анализ. Аудит)
The method of combining forecasts has already proven itself in practice as a reliable and effective way to improve the accuracy of economic forecasting. But this technique has several disadvantages. Today, one of the ways to improve the method of combining forecasts is to find the possibility of attracting expert information as a tool for correcting the obtained forecast results. This article is devoted to the use of an expert method of pairwise comparisons for constructing the weights of the combined forecast as one of the options for which you can use expert information when combining forecasts. The proposed methodology has been applied in practice for the economic time series of some products of industrial production in Russia. An assessment was made of the effectiveness of using the method of pairwise comparisons for combining forecasts, and based on the results obtained, a forecast of the development of the economic indicators under consideration was proposed.